From a Theory-Centric View of Social Research to a Data-Centric Approach - Stefanizzi, Sonia (Italian Sociological Review, 2022)
Digital data have become so pervasive that they are the main resource used in scientific research, business and society. With reference to scientific research, a data-centric approach is emerging in all scientific disciplines. The article argues that data centrism does not mean the absence of theory. In fact, as will be shown, data are always produced in relation to and to precise expectations and conceptual schemes. Just as the algorithms that are used to analyze huge amounts of data are “material executors” of actions predetermined beforehand. A relevant aspect of data centrism is that the large amount of data available is closely linked to a revolution in the communication of research results that becomes Open Science. The link between Big Data and Open Data is, therefore, the true revolutionary contribution of data-centrism. In fact, the dissemination of data using open formats (Open Data) is able to provide new opportunities in terms of greater transparency on the part of the producers of the data. The data-centric approach allows us to tackle problems that in the past were considered difficult or impossible to analyze, it also raises other questions related to data quality and ethics such as the right to privacy, transparency in accessing public data, and fair treatment of predictive techniques. [...]